JAPANESE-MALAY E-DICTIONARY WITH VOICE RECOGNITION - Mohd Afifi, Aini Fadhilah (Universiti Teknologi PETRONAS, 2006)
This report is to give a brief introduction to a project that is going to be done under the Artificial Intelligent field. This project is based on the natural language processing which an electronic dictionary will be built for Japanese-Malay language translation. The intelligent part of this e-dictionary is that it will be integrated with voice recognition program to allow user to interact with it. The e-dictionary will be built similar to the current e-dictionary available in the market today. The end-product may not be a full-functioning device by itself, but it may be a prDlmype to be tested on a computer. The program for the e-dictionary will be using Microsofi~ Visual Basic 6.0 for the system. As voice recognition system will be added to the system, the speech recognition engine and text-to-speech engine available for 'viicrosoft Visual Basic 6.0 language will be used in order to take advantage of its library. 'vficrosofi: Office Access 2003 will be used for the database of this system.